2017
DOI: 10.21475/ajcs.17.11.08.pne445
|View full text |Cite
|
Sign up to set email alerts
|

Copper (Cu) stress affects carbon and antioxidant metabolism in Coffea arabica seedlings

Abstract: Although copper is a micronutrient essential for the normal development of plants, both insufficient and supra optimal doses can disrupt the functioning of metabolism and the production of biomass. To study the biochemical and physiological impacts of deficiency and excess of copper in coffee, we treated 6-month-old seedlings of Coffea arabica L. Catuaí cultivar to three copper treatments: control (0.03 ppm), excess (0.12 ppm) and deficiency (0 ppm) for 60 days. The changes in levels of photosynthetic pigments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Mazhar et al [107] have reported that ZnO NP priming has increased SOD, POD, and CAT activity in rice under drought stress. SOD is the first line of defense against ROS-induced oxidative and cellular damage [173]. Seed priming with Ag NPs and TiO 2 NPs improved SOD, POD, CAT, and carotenoid contents in Solanum Lycopersicum [69,89].…”
Section: Effects On Plant Antioxidant Defense Systemsmentioning
confidence: 99%
“…Mazhar et al [107] have reported that ZnO NP priming has increased SOD, POD, and CAT activity in rice under drought stress. SOD is the first line of defense against ROS-induced oxidative and cellular damage [173]. Seed priming with Ag NPs and TiO 2 NPs improved SOD, POD, CAT, and carotenoid contents in Solanum Lycopersicum [69,89].…”
Section: Effects On Plant Antioxidant Defense Systemsmentioning
confidence: 99%
“…The treatments with the application of Cu NPs in 125 and 250 mg L −1 doses presented an increase of 260% and 86%, respectively, in comparison to the Control. This is because SOD acts as the first line of defense against ROS [45,70] generated by stress caused by Cu NPs. In addition, the SOD activity is also induced by metal ions such as Cu, or by the increase in singlet oxygen levels [71].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Therefore, its activity is directly related to the stress caused by the application of Cu NPs [62]. An increase in CAT activity is dependent on the concentration of H 2 O 2 [70]. Thus, there is a correlation between the components of the ROS elimination systems (e.g., CAT and SOD) [74].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Frontiers in Environmental Science frontiersin.org comprising different anti-oxidant enzymes (APX, CAT, POD, and SOD: Table 2) (Afridi et al, 2019). SOD works as the first defense line against the oxidative stress created by ROS (Dos Santos et al, 2017). Zn supplementations enhanced the antioxidant activities (Figure 3) and reduced the HMs-induced oxidative damages in maize (Salam et al, 2022).…”
Section: Zinc Strengthens Anti-oxidant Activities Under Heavy Metals ...mentioning
confidence: 99%